Criminal Liability of Members of the Police of the Republic of Indonesia as Perpetrators of Criminal Acts in the Bali Police - Sulaksana, I Gusti Bagus; Wiratny, Ni Ketut; Suandika, I Nyoman (Pelopor Publikasi Akademika, 2025)
Police officers as law enforcers have a central role in law enforcement. Problems arise when police officers actually break the law or commit crimes. The crimes committed not only violate criminal law, but also violate the ethics and code of the police profession. Based on this description, the problem can be formulated as follows: How is the responsibility of police officers who commit crimes in the Bali Regional Police (Polda) and What are the obstacles to imposing sanctions for police officers who commit crimes in the Bali Regional Police (Polda). The responsibility of police officers who commit crimes includes accountability for the code of ethics and criminal accountability through general justice and its resolution internally within the institution, namely through a disciplinary hearing by the Indonesian National Police Code of Ethics Commission (KKEP). Obstacles to the application of sanctions for police officers who commit crimes in the Bali Regional Police are in the form of internal problems within the Polri structure, such as limited facilities and infrastructure, information networks, number of personnel, and budget support. In addition, there are also external obstacles that come from the community, such as lack of evidence and witnesses, community apathy, and lack of supporting facilities